Study Of Prevalence Of Patellofemoral Pain Syndrome In Utensil Cleaning Females Of Catering Profession - Doshi, Samruddhi; Sagar, Javid H (Journal of Neonatal Surgery, 2025)
Background: PFPS is pain behind or around the patella that worsens with specific workouts or movements. Examples of these exercises are squatting, ascending stairs, jogging, running, jumping, extending the knee, getting up after prolonged sitting, and other weight-bearing exercises. The typical symptoms of PFPS are pain behind or around the patella, which affects 22.7% of the general population. The prevalence of "anterior knee pain" is considerable, occurring in 22 out of every 1,000 individuals annually. Method: The study aimed to investigate the prevalence of patellofemoral pain syndrome in utensils cleaning females of catering profession in Kolhapur city. Materials: Subjects were selected from catering centers and assessed using the Patellar tilt test and Kujala questionnaire. Inclusion exclusion criteria were considered, and subjects willing to participate were included after receiving an explanation of the study’s nature. Result: In this study, participants aged 25 to 40 had an average age of 32.19 ±5.39 years. The prevalence of Patellofemoral pain syndrome in utensils-cleaning females of the catering profession was 70.59%. The females experiencing anterior knee pain had an average working experience of 8.16±4.74 years and an average of 9.83±2.50 daily working hours. Previous studies showed varying levels of pain severity. In contrast, in this study, at rest, 32.35% had no pain, 61.76 % had mild pain, and 5.88% had moderate pain, while during movement, 39.22% had severe pain, 32.35% had moderate pain, and 28.43% had mild pain. The patellar tilt shows positive in 70.59% of the population, indicating PFP symptoms. The kujala/akps shows that out of the 102 participants, 65.69% had low scores, 15.69% had fair scores, 17.65% had good scores, and only 0.98% had excellent scores, indicating a high prevalence of PFPS in utensils cleaning females of catering profession. Conclusion: This study highlights a high prevalence of the patellofemoral pain syndrome under study, with significant implications for the functional status and pain levels of individuals affected. The findings underscore the need for improved diagnostic and treatment strategies, particularly those aimed at alleviating pain during movement and enhancing knee function. Further research into the causes and effective management of this condition is essential for improving the health and quality of life of those affected.